The use of rock phosphate and phosphate solubilising fungi (Aspergillus niger) to improve the growth and the yield of upland rice on typic Kandiudalf - Asuming-Brempong, S.; Anipa, B. (West African Journal of Applied Ecology, 2014)
Field experiment was conducted to study the effect of rock phosphate (RP) and phosphate solubilizing fungi application on upland rice yield intercropped with pigeon pea from 2009 to 2011 at the Agricultural Research Centre, Kade, University of Ghana. In the first year, the main plot treatment consisted of five levels of phosphate fertilizer viz. 0 kg/ha P2O5, 40 kg/ha P2O5 RP, 80 kg/ha P2O5 RP, 120 kg/ha P2O5 RP and 45 kg/ha P2O5-triple super phosphate (TSP), while the planting dates of pigeon pea was set up as subplot (40 DAS –pigeon pea planted 40 days after sowing rice seed and 80 DAS- pigeon pea planted 80 days after sowing rice). In the second year, phosphate fertilizer was the main plot treatment, consisting of (0 kg/ha P2O5, 45 kg/ha P2O5 RP, 90 kg/ha P2O5 RP and 45 kg/ha P2O5 TSP), and the subplot treatment was inoculated and uninoculated with phosphate solubilising fungi Aspergillus niger. The highest grain yield of 1.051 t/ha was obtained with the 120 kg P2O5 /ha RP followed by the 40 kg P2O5 /ha RP. Phosphate levels did not significantly influence the grain yield in the first year (p = 0.08) but planting pigeon pea as an intercrop at the different planting dates had a significant positive effect on both the grain and straw yields of rice (p = 0.016, .07). There was no significant interaction between the use of different phosphorus levels and the different planting dates of pigeon pea (p = 0.348). In the second year, phosphate levels had significant influence on grain yield (p = 0.014) and the highest grain and straw yields occurred where TSP and Aspergillus niger were used to plant rice. Inoculating rice with or without Aspergillus niger had no significant influence on grain yields (p = 0.447). No significant interaction existed between phosphate levels and level of inoculation (p = 0.206). The use of TSP and Aspergillus niger to grow rice improved rice yield followed by 45 kg P2O5/ha RP + Inoculation.
Keywords: rock phosphate; phosphate solubilising fungi; typic Kandiudalf; upland rice